The Gastroprotective Effect of DLBS2411 for High-Risk Gastrointestinal Patients: Case Series in Inflammatory Pain Condition - Rizaldy Taslim Pinzon; Abraham Al Jody; Nicholas Adriel Pinzon (PT Dexa Medica, 2025)
Chronic pain is a common and distressing problem for the population. The cyclooxygenase (COX)-2 selective and nonselective nonsteroidal anti-inflammatory drugs (NSAIDs) are widely used in managing acute and chronic pain. Research has provided a greater understanding of the risks of gastrointestinal, cardiovascular, and renal events associated with NSAID use. Proton pump inhibitors (PPIs) are widely prescribed due to their gastroprotective effects in NSAID users. However, PPIs also have several acid-inhibition-related and unrelated adverse effects that limit their use in high-risk patients. We report five patients suffering from painful inflammatory pain (flare rheumatoid arthritis, painful knee bursitis, and osteoarthritis). In this case series we evaluate the use of DLBS2411 as an alternative to PPIs. Our study suggests that DLBS2411 can be a safe alternative to PPIs for gastrointestinal high-risk patients who require anti-inflammatory agents.